The primary health care nurse of the future: Preliminary evaluation of the Nurse Navigator role in integrated care. Issue 5 (October 2018) - McMurray, Anne; Ward, Lauren; Johnston, Kate; Yang, Lei; Connor, Martin
Abstract: Problem/background: Nurse navigators in the Gold Coast Integrated Care program are co-located in general practices and a community coordination centre providing enhanced access to care for chronic disease patients through a multidisciplinary, multiservice, multilevel primary health care model, which has yet to be evaluated. Aim: To evaluate the context, mechanisms and processes of nurse navigators' practice after one year. Methods: The theoretical framework of realist synthesis framed the evaluation examining the relationships between context (the program), mechanisms and processes of enhancing patient access to care. Focus groups were conducted with seven of eight nurse navigators and 33 randomly selected patients. Surveys were completed by 55 general practitioners and 19 practice nurses, analysed using descriptive statistics and content analysis of free text. Patient and nurses' focus group data were thematically analysed. Findings: All patients reported high satisfaction with the nurse navigators. Themes from the nurse navigator group included enthusiasm and engagement; constraints related to workload, variability and time; desire for a professional 'voice', and issues with the technological environment. General practitioners and practice nurses identified the importance of information, communication, coordination, advocacy, liaison and patients' positive health outcomes, with 73% of GPs and 84% of PNs reporting being satisfied with the NN role. Discussion: The role is effective in enhancing access to care for chronic disease patients by bridging the gap between primary and secondary care. Their expertise and collaborative liaison with multidisciplinary health professionals has been well accepted by General Practitioners, Practice Nurses, patients and the nurse navigators themselves. Further development of the role over time is expected to show an impact on patient outcomes and value to the health system in the ongoing evaluation. Conclusion: The role and scope of practice needs to be articulated across different contexts, and to advance evidence for practice and education for primary health care.